Harmonization of labor legislation of member states of the EAEU - Maxim Shilo (Научно-аналитический вестник Института Европы РАН, 2019)
The article investigates the issue of regional economic integration in the countries of the Eurasian economic Union (hereinafter-the EAEU). The relevance of the study is due to the fact that regional integration needs further development of legal regulation of the legislation of the EAEU member States. Economic integration is impossible without legal integration. Legal integration is that there is a Union of national labor laws, their optimization. In order to carry out a coordinated policy in the social and labor sphere of the EAEU member States, the Bases of the EAEU legislation on labor were developed, which are of a recommendatory nature. It is revealed that the harmonization of labor legislation of the EAEU member States involves not only the creation of The foundations of the EAEU legislation on labor, but also the harmonization of national legislation with them. In this regard, recommendations are given to improve the labor legislation of the Republic of Belarus.